POTENTIAL EFFECT OF RHIZOBACTERIA Streptomyces sp. AND Bacillus sp. TO GEMINIVIRUS INFECTION AND RED CHILI (Capsicum annum L.) QUALITY PRODUCTION - Azizah Ridha Ulilalbab; Sri Sulandari; Triwidodo Arwiyanto; Sedyo Hartono (Jurnal Agroteknologi, 2023)
The chili yellow leaf curl disease is one of the biggest obctacle in chili’s production in Indonesia. This diseases only transmitted by whitefly (Bemisia tabaci). One of the disease controlling method is by using Plant Growth Promoting Rhizobacteria (PGPR) to reduce pesticide application for the health and environment. The aim of this research is to find out the effectiveness of Streptomyces sp. and Bacillus sp. in supressing yellow leaf curl disease, plant growth and chili harvest. This research has conducted at the experimental farmer’s field in Harjobinangun, Pakem, Sleman, Special Region of Yogyakarta. Using varieties of chili Twist 42, Streptomyces isolates which from Bacteriology Laboratory collection’s with 10-8 CFU/ml and Bacillus isolates which is from Mycrobiology Laboratory collection with  10-8 CFU/ml. The result of this research showed that the treatment of combination between Bacillus sp. and Streptomyces sp. could decrease and supress disease incidence and disease intensity if it compared with others treatment. Parameters of plant growth included plant high, stem diameter, root length, root volume and number of productive branch showed that single of Streptomyces sp. and Bacillus sp. without combination were better than combination and untreated.  The single application Streptomyces sp. or Bacillus sp. could increase amount of total number and weight of fruits.